Effects of Clarias, Soy Protein, Moringa with Vitamin D Biscuit and Anti-TB Drugs on Blood Serum and Biochemical Profile of Tuberculosis-infected Rats - Fariani Syahrul; Annis Catur Adi; Wizara Salisa; Noni Angelina Tazky Aulia; Livia Bellatrix Roberts; Muhammad Atoillah Isfandiari (Media Gizi Indonesia, 2026)
The surge of tuberculosis (TB) in Indonesia, reaching over 385 cases per 100,000 population in 2024, presents an evident public health challenge. Primary drug-based (OAT/anti-TB drugs) therapy has adverse effects, affecting patient compliance and health outcomes. Nutritional therapy derived from animal-plant protein enriched with vitamin D has been offered as an adjunct therapy. This study investigated the effectiveness of catfish-derived biscuit substitutes, isolated soy protein, and moringa flour enriched with vitamin D in improving physical and immunological outcomes. Using a completely randomized design, the research process encompassed product development and pre-clinical testing in 35 adult white male Rattus norvegicus aged 8 weeks weighing 130-140 grams which were randomly divided into five groups, namely negative control (K0), Mycobacterium tuberculosis (Mtb)-injected (K1), Mtb-injected + OAT (anti-tuberculosis drugs), Mtb-injected + OAT + 1,000 IU vitamin D biscuit (D1), and Mtb-injected + OAT + 2,000 IU vitamin D biscuit (D2), and were observed for a total of 46 days. H37Rv Mycobacterium tuberculosis (Mtb) was injected into as much as 106 colonies/ml of 100 µL. Complete blood count was measured using the HEMAVET method, albumin and total protein were determined using spectrophotometry, and C-reactive protein (CRP) was analyzed using enzyme-linked immunosorbent assay (ELISA). Although product administration did not show a significant impact towards erythrocytes (p>0.05), it was still able to improve BMI within normal limits, increase albumin and total serum protein values, maintain leukocyte, hemoglobin, and hematocrit within standard values, lower CRP levels.